PENERAPAN PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V SD NEGERI 067257 MEDAN - Farhani Atsina Wardah; Silalahi, Beta Rapita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' learning outcomes in the subject of Naturaland Social Sciences (IPAS) through the application of the Project Based Learning(PjBL) learning model. The subjects in this study were grade V students of SDNegeri 067257 Medan. The method used was Classroom Action Research (PTK)which was carried out in two cycles where each cycle consisted of two meetings.Each cycle consisted of the planning, implementation, observation, and reflectionstages. Data collection techniques were carried out through learning outcometests, observation of student activities, and documentation. The results of thestudy showed that the application of the Project Based Learning (PjBL) modelcould improve students' learning outcomes. This can be seen from the increase inthe average value of student learning outcome completion from the pre-cycle of38% to cycle I obtaining a score of 77% and then to cycle II with a score of 92%.Thus, the application of Project Based Learning has proven effective in improvingthe learning outcomes of grade V students of SD Negeri 067257 Medan.